Single crystal growth of Eu2CuSi3 intermetallic compound by the floating-zone method - Cao, Chongde; Löser, Wolfgang; Behr, Günter; Klingeler, Rüdiger; Leps, Norman; Vinzelberg, Hartmut; Büchner, Bernd (Journal of crystal growth, 2011)
Large single crystals of the Eu2CuSi3 intermetallic compound have been successfully grown by a vertical floating-zone method with optical heating. Differential thermal analysis reveals that Eu2CuSi3 melts congruently at 1422°C. The single crystals grown at velocities of 3-5mm/h show a preferred growth direction close to crystallographic [100] orientation with inclination angles of about 16-20°. The suppression of evaporation of volatile elements and the control of the floating-zone temperature play a main role in the stability of the growth process. The crystals are Cu-depleted with respect to the nominal Eu2CuSi3 stoichiometry. Both magnetic susceptibility and electrical resistivity measured on oriented single crystalline Eu2CuSi3 samples reveal significant anisotropy with an easy magnetic c-axis and ferromagnetic ordering at TC=34K.
Available online 10 December 2010
Im Titel sind die Zahlen 2 und 3 tiefgestellt
Gesehen am 27.06.2022